2012
DOI: 10.1139/o2012-026
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin induces de-differentiation of activated hepatic stellate cell

Abstract: Hepatic stellate cells (HSC) play a key role in liver fibrogenesis. Activation of PPARγ and inhibition of fibrogenic molecules are potential strategies to block HSC activation and differentiation. A number of natural products have been suggested to have antifibrotic effects for the de-activation and de-differentiation of HSCs. The purpose of this study was to investigate the in vitro effects of capsaicin on HSC de-activation and de-differentiation. The results demonstrated that capsaicin induced quiescent phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 47 publications
3
25
0
Order By: Relevance
“…It is consumed worldwide as a food additive, especially in Latin‐American and Asian countries . CPS has several beneficial properties such as anti‐inflammatory and antioxidative . The amount of CPS (0.01%) used in this study is similar to the quantity reported by Li et al.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…It is consumed worldwide as a food additive, especially in Latin‐American and Asian countries . CPS has several beneficial properties such as anti‐inflammatory and antioxidative . The amount of CPS (0.01%) used in this study is similar to the quantity reported by Li et al.…”
Section: Discussionsupporting
confidence: 70%
“…TGF‐β1 is the main profibrogenic cytokine related to the activation of HSCs and we have previously shown that CPS strongly affects TGF‐β1 secretion . We show here that CPS does not affect the early responders Smad6 and Smad7, but clearly affects later events (αSMA, Col1a1, and Lox upregulation) following TGF‐β1 stimulation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…GRX cells represent a heterogeneous population that can be induced to have majority activated or quiescent cells . Here, we showed for the first time that exogenous expression of Cav‐1 (GRX EGFP‐Cav1 ) induced the majority of the GRX population into an activated‐like HSC state.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, culture‐activated HSC can be phenotypically and functionally reversed to a quiescent‐like phenotype by forced expression of PPARγ [Hazra et al, ]. On this premise, it was already demonstrated that PPARγ mRNA expression was increased in GRX quiescent‐like cells [Guimaraes et al, ; Bitencourt et al, ].…”
mentioning
confidence: 99%